2002
DOI: 10.1056/nejmoa011892
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Injection of Botulinum Toxin for the Treatment of Wrist and Finger Spasticity after a Stroke

Abstract: Intramuscular injections of botulinum toxin A reduce spasticity of the wrist and finger muscles and associated disability in patients who have had a stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
376
0
14

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(418 citation statements)
references
References 17 publications
28
376
0
14
Order By: Relevance
“…From the 98 selected papers, six fulfilled all inclusion criteria [8][9][10][11][12][13] . Despite one study 8 presented the described criteria, it was excluded from the metaanalysis because it did not present comparable data to be analysed ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the 98 selected papers, six fulfilled all inclusion criteria [8][9][10][11][12][13] . Despite one study 8 presented the described criteria, it was excluded from the metaanalysis because it did not present comparable data to be analysed ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The spasticity is variable from patient to patient and individualised scales will be necessary to measure specific goals 14 . Brashear et al 13 analysed functional aspects of post-stroke patients with wrist and finger spasticity submitted to intra-muscular injection of BTX-A or placebo. These authors observed significant improvement of functional disability in pa- tients that received BTX-A when compared to placebo group, emphasising the importance of BTX-A in clinical rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Contracture and change in the morphologic features of muscle 36 contribute to a flexed posture, but poor motor control with weakness, not hypertonia, is the primary cause of disability. 37 In a randomized trial, the injection of botulinum toxin into the muscles of the arm reduced excessive flexion and the associated pain, spasms, or postures that interfered with patients' self-care, 38 but the induced muscle weakness usually does not improve the functional use of the hand. The injection must be followed by stretching exercises and treatment of pain that may exacerbate the hypertonicity.…”
Section: Targeted Therapymentioning
confidence: 99%
“…Seven BoNT serotypes are known to exist (A-G), all of which are produced by strains of the bacterium Clostridium botulinum. BoNT causes the paralytic syndrome botulism, but also holds therapeutic application in the treatment of dystonias [3][4][5][6], spasticity [7,8], facial rhytides [9], axillary hyperhidrosis [10,11], and some pain syndromes [12,13].…”
Section: Introductionmentioning
confidence: 99%